Vekāyi-i Devlet-i Aliyye-i Osmâniyye ; Zeyl-i târîh-i Hayrullâh Efendi - Hayrullah Efendi, 1818-1866. (İstanbul [İstanbul] [İstanbul] [İstanbul] İstanbul İstanbul [İstanbul] İstanbul)
18 cilt 2 ciltte